Frontal and Cerebellar Atrophy Supports FTSD-ALS Clinical Continuum - Pizzarotti, Beatrice; Palesi, Fulvia; Vitali, Paolo; Castellazzi, Gloria; Anzalone, Nicoletta; Alvisi, Elena; Martinelli, Daniele; Bernini, Sara; Cotta Ramusino, Matteo; Ceroni, Mauro; Micieli, Giuseppe; Sinforiani, Elena; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Frontotemporal Spectrum Disorder (FTSD) and Amyotrophic Lateral Sclerosis (ALS) are neurodegenerative diseases often considered as a continuum from clinical, epidemiologic and genetic perspectives. We used localized brain volume alterations to evaluate common and specific features of FTSD, FTSD-ALS and ALS patients to further understand this clinical continuum. Methods: We used voxel-based morphometry on structural MRI images to localize volume alterations in group comparisons: patients (20 FTSD, seven FTSD-ALS, 18 ALS) versus healthy controls (39 CTR), and patient groups between themselves. We used mean whole-brain cortical thickness (¯CT) to assess whether its correlations with local brain volume could propose mechanistic explanations of the heterogeneous clinical presentations. We also assessed whether volume reduction can explain cognitive impairment, measured with frontal assessment battery, verbal fluency and semantic fluency. Results: Common (mainly frontal) and specific areas with reduced volume were detected between FTSD, FTSD-ALS and ALS patients, confirming suggestions of a clinical continuum, while at the same time defining morphological specificities for each clinical group (e.g. a difference of cerebral and cerebellar involvement between FTSD and ALS). ¯CT values suggested extensive network disruption in the pathological process, with indications of a correlation between cerebral and cerebellar volumes and ¯CT in ALS. The analysis of the neuropsychological scores indeed pointed towards an important role for the cerebellum, along with fronto-temporal areas, in explaining impairment of executive and linguistic functions. Conclusions: We identified common elements that explain the FTSD-ALS clinical continuum, while also identifying specificities of each group, partially explained by different cerebral and cerebellar involvement.